2016
DOI: 10.21037/atm.2016.07.07
|View full text |Cite
|
Sign up to set email alerts
|

Towards tumor immunodiagnostics

Abstract: Immunodiagnostic markers applicable on tissue or cytologic material may be prognostic or predictive of response to immunomodulatory drugs and may also be classified according to whether they are cell-specific or tumor-tissue-specific. Cell-specific markers are evaluated under the microscope as (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 130 publications
(135 reference statements)
0
10
0
1
Order By: Relevance
“…As a result of it, immunotherapies targeting and blocking immune checkpoint, such as CTLA-4 and PD-1 are newly applied to patients with ccRCC during the last decade. CD3 + tissue infiltrating lymphocytes (TILs) forming memory T-cell and CD8 + TILs forming cytotoxic T-cell play a key role in immune defense (14). Local immune response in ccRCC, such as CD3 + and CD8 + TILs, has been analyzed in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of it, immunotherapies targeting and blocking immune checkpoint, such as CTLA-4 and PD-1 are newly applied to patients with ccRCC during the last decade. CD3 + tissue infiltrating lymphocytes (TILs) forming memory T-cell and CD8 + TILs forming cytotoxic T-cell play a key role in immune defense (14). Local immune response in ccRCC, such as CD3 + and CD8 + TILs, has been analyzed in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular marker of pan-macrophage is CD68, while M2-like macrophage is CD163 and CD23. 27 Studies have shown that the development from precancerous cervical lesions to cancer was associated with a large number of infiltrated CD68 macrophages. 28 , 29 Our study found that the intratumoral density of CD68-positive cells was not related to clinical features (including FIGO stage and lymph node metastasis), but the density of CD163-positive cells was associated with FIGO stage and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A still unmet need in the clinical application of checkpoint inhibitors concerns predictive markers for these drugs despite that three companion diagnostic PD-L1 assays have recently been FDA approved for an equal number of PD1 or PD-L1 blocking drugs (6). The clinical value of these assays remains to be evaluated in practice but it is already known that patients are concordantly identified with all assays in cases with true over-expression of PD-L1 (>50% positive cancer cells); in the absence of underlying up-regulating genetic alterations, PD-L1 is transiently expressed, and staining of tumor tissues is heterogeneous.…”
Section: Overview Of Advances In Cancer Immunotherapymentioning
confidence: 99%
“…Surrogate predictive markers of response to PD1/ PD-L1 inhibitors may include simple IHC for mismatch repair (MMR) proteins in cases with suspected MMR deficiency or tumor mutational load. The latter may be evaluated in association with specific mutation characteristics (i.e., clonal mutations, specific gene mutations) or with stromal TILs density (6). The possibility to use such markers for predicting response to currently used immunotherapeutic drugs and/or to conventional chemotherapeutics is progressively investigated.…”
Section: Overview Of Advances In Cancer Immunotherapymentioning
confidence: 99%